Associations of ATP-Sensitive Potassium Channel’s Gene Polymorphisms With Type 2 Diabetes and Related Cardiovascular Phenotypes - Liu, Cheng; Lai, Yanxian; Guan, Tianwang; Zhan, Junfang; Pei, Jingxian; Wu, Daihong; Ying, Songsong; Shen, Yan (Frontiers in Cardiovascular Medicine, 2022)
Type 2 diabetes (T2D) is characterized by high blood glucose levels, but is increasingly recognized as a heterogeneous syndrome, especially its multiple discrete cardiovascular phenotypes. The genetic variation plays a key role in heterogeneity of diabetic cardiovascular phenotypes. In present study we investigated possible associations of ATP-sensitive potassium channels (KATP) variants with cardiovascular phenotypes among Chinese T2D patients. 636 T2D patients and 634 non-diabetic individuals were recruited to the study. 9 KATP variants were determined by MassARRAY. KATP rs2285676 (AA+GA, OR=1.43, 95% CI: 1.13-1.81, P=0.003), rs1799858 (CC, OR=1.42, 95% CI: 1.12-1.78, P=0.004) and rs141294036 (CC, OR=1.45, 95% CI: 1.15-1.83, P=0.002) were associated with increased T2D risk. After at least median 45.8-months follow-up, the 3 variants were further associated with risks of diabetic related cardiovascular conditions as follows: new-onset/recurrent acute coronary syndrome (ACS) (rs2285676/AA+GA, HR=1.37, 95% CI: 1.10-1.70, P=0.005; rs141294036/TT+CT, HR=1.59, 95% CI: 1.28-1.99, P<0.001), new-onset stroke (rs1799858/CC, HR=2.58, 95% CI: 1.22-5.43, P=0.013; rs141294036/CC, HR=2.30, 95% CI: 1.16-4.55, P=0.017), new-onset heart failure (HF) (rs1799858/TT+CT, HR=2.78, 95% CI: 2.07-3.74, P<0.001; rs141294036/TT+CT, HR=1.45, 95% CI: 1.07-1.96, P=0.015), and new-onset atrial fibrillation (AF) (rs1799858/TT+CT, HR=2.05, 95% CI: 1.25-3.37, P=0.004; rs141294036/CC, HR=2.31, 95% CI: 1.40-3.82, P=0.001). In particular, the CC genotype of rs1799858 (OR=2.38, 95% CI: 1.11-5.10, P=0.025) and rs141294036 (OR=1.95, 95% CI: 1.04-3.66, P=0.037) were only associated with ischemic stroke risk while its counterpart genotype (TT+CT) with the risks of HF with preserved ejection fraction (rs1799858, OR=3.46, 95% CI: 2.31-5.18, P<0.001) and HF with mildly reduced ejection fraction (rs141294036, OR=2.74, 95% CI: 1.05-7.15, P=0.039). Furthermore, the 3 variants were associated with increased risks of abnormal serum levels of triglyceride (≥ 1.70 mmol/L), low-density lipoprotein cholesterol (≥ 1.40 mmol/L), apolipoprotein B (≥ 80 mg/dL), apolipoprotein A-I level (< 120 mg/dL), lipoprotein(a) (≥ 300 mg/dL) and high-sensitivity C-reactive protein (≥ 3.0 mg/L) but exhibited heterogeneity (all P<0.05). KATP rs2285676, rs1799858 and rs141294036 were associated with increased risks of T2D and its related cardiovascular phenotypes (ACS, stroke, HF and AF), but showing heterogeneity. The 3 KATP variants may be promising markers of diabetic cardiovascular events for early and “genotype-phenotype” oriented prevention and treatment strategies.